The Effect of Primary Open Angle Glucoma on Progression of Diabetic Retinopathy in Type 2 Diabetic Patients in Alsayem Eye Hospital - Mohamed Osman, Zuhal Alhassan; Omar, Tarig; Salim, Mahmoud Abdula (Gezira Journal of Health Sciences, 2017)
Background: Diabetic retinopathy is a serious complication of diabetes. Five percent of patients of type 2 diabetes (NIDDM) have signs of eye problems when diabetes is diagnosed.Control of blood sugar, blood pressure and cessation of smoking, have an important role in slowing the progression of retinopathy and other eye problems caused by diabetes.  Objectives: To determine whether there is a difference in progression of diabetic retinopathy among patients with and without primary open angle glucoma (POAG). Design: comparative cross –sectional study.  Participants: 160 patients who were on regular follow up and treatment in both retina and glaucoma clinics in Al-Sayem Eye Hospital were enrolled in the study. Patients were divided into 2 groups, the study group: included 80 patients who were type 2 diabetics with POAG (group A) .The control group were having type 2 diabetes without POAG (group B).The patients were compared for the grade of diabetic retinopathy according to international clinical diabetic retinopathy disease severity scale. For maculopathy patients were also classified according to international clinical diabetic macular edema disease severity scale. Risk factors for both groups were studied as follow: age, duration of DM, control of DM, systemic hypertension and smoking. Results: In multivariate analyses adjusting for above risk factors and examination for both groups. Diabetic retinopathy was not found in the study group (100%), compared to patients in the control group (patients without POAG) in which no diabetic retinopathy was found in only 8.8%. Mild NPDR was found in 14 patients (43.7%), moderate non prolifrative diabetic retinopathy(NPDR) was observed in 70 patients (32.5%), and severe NPDR in 24 patients (15%). Mild maculopathy was observed in only 4 patients in the study group (5%), all of them were poorly controlled with duration of diabetes of >11 years.In the control group, the majority of patients had no diabetic macular edema(DME) (65%). Mild DME was found in 48 patients (30%). Eight patients only in the control group had moderate DME. Conclusion: POAG and increased cup disc ratio are associated with a lower risk of DR, particularly vision-threatening retinopathy.